Hasil Evaluasi Kelompok Kecil Bahan Ajar Mata Kuliah Statistika Matematika Berbasis Pemecahan Masalah Serta Bernuansa Islami - Utami, Nita Putri; Kosim, Muhammad (Math Educa Journal, 2021)
Tadris Mathematics is one of the study programs at UIN IB Padang with the vision "To produce character, professional and competitive mathematics education graduates in 2037". In order for this vision to be realized, of course there must be interesting interactions between lecturers and students in lectures. Meanwhile, the reality that occurs in lectures, there are still many students who are passive and result in many student scores that have not passed after taking the exam. One of the ways that a lecturer can do to overcome this problem is by developing Mathematical Statistics teaching materials based on problem solving and Islamic nuances. The formulation of the problem in this research is how the process and results of the development of Mathematics Statistics Subject Teaching Materials Based on Problem Solving and Practical Islamic Nuances in small group evaluations. This research is a development research with the Plomp development model using Tesmer's formative evaluation. Data collection techniques using practicality questionnaires from the teaching materials developed. From the results of the study, it was obtained a value of 79% with practical criteria that had been developed through a small group trial process.